1988
DOI: 10.1002/syn.890020507
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of nerve terminal populations: Synaptic vesicle‐associated proteins as markers for synaptic density in the rat neostriatum

Abstract: This study has assessed the contributions of the corticostriatal fibers, the ascending striatopetal fibers, and the intrinsic neostriatal neurons to the nerve terminal population found in the rat neostriatum (caudatoputamen). For this purpose, we have analysed the levels of two different synaptic vesicle-associated proteins, synapsin I and protein p38 (also called synaptophysin), in the neostriatum after specific lesions. Our results indicate that 45-50% of the synaptic vesicle proteins in the rat neostriatum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

1992
1992
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(34 citation statements)
references
References 50 publications
1
32
0
1
Order By: Relevance
“…To determine the spatial relationship between nerve endings and TNF-producing macrophages in spleen, we looked for the distribution pattern of the presynaptic vesicleassociated protein synaptophysin, a synaptic vesicle protein (24,25). Synaptophysin punctae were distributed in networks in the parenchyma of the white pulp and around the central artery.…”
Section: Nerve Terminals In the Spleen Are Found Adjacent To Tnf-prodmentioning
confidence: 99%
“…To determine the spatial relationship between nerve endings and TNF-producing macrophages in spleen, we looked for the distribution pattern of the presynaptic vesicleassociated protein synaptophysin, a synaptic vesicle protein (24,25). Synaptophysin punctae were distributed in networks in the parenchyma of the white pulp and around the central artery.…”
Section: Nerve Terminals In the Spleen Are Found Adjacent To Tnf-prodmentioning
confidence: 99%
“…In the present study we found no changes in expression of the mRNA for synaptophysin in animals with a flattened corticosterone rhythm. SynaptophysinFa synaptic protein with roles in vesicle biogenesis and fusion (Elferink and Scheller, 1995)Fis a wellestablished synaptic marker (Walaas et al, 1988;Eastwood and Harrison, 1995). Furthermore, it has been shown that synaptophysin protein correlates well with synaptic number when this is measured by morphometric methods (McEwen et al, 1999;Brake et al, 2001), and also that synaptophsyin mRNA correlates with synaptophysin protein levels (see Eastwood and Harrison, 1995).…”
Section: Corticosterone-induced Changes In Hippocampal Expression Of mentioning
confidence: 99%
“…The homo-oligomeric protein is a major calcium-binding component of synaptic vesicles [ 18] and it seems to play a crucial role in vesicular uptake and release of secondary compounds at the synap ses [19]. Therefore, immunostaining with monoclonal an tibodies against synaptophysin has been used to investi gate synapse formation during ontogenesis [20] and to quantify nerve terminal populations [21,22].…”
mentioning
confidence: 99%